Burkholderia ubonensis Meropenem Resistance: Insights into Distinct Properties of Class A β-Lactamases in Burkholderia cepacia Complex and Burkholderia pseudomallei Complex Bacteria - Nawarat Somprasong (American Society for Microbiology, 2020)
ABSTRACT Burkholderia pseudomallei, the founding member of the B. pseudomallei complex (Bpc), is a biothreat agent and causes melioidosis, a disease whose treatment mainly relies on ceftazidime and meropenem. The concern is that B. pseudomallei could enhance its drug resistance repertoire by the acquisition of DNA from resistant near-neighbor species. Burkholderia ubonensis, a member of the B. cepacia complex (Bcc), is commonly coisolated from environments where B. pseudomallei is present. Unlike B. pseudomallei, in which significant primary carbapenem resistance is rare, it is not uncommon in B. ubonensis, but the underlying mechanisms are unknown. We established that carbapenem resistance in B. ubonensis is due to an inducible class A PenB β-lactamase, as has been shown for other Bcc bacteria. Inducibility is not sufficient for high-level resistance but also requires other determinants, such as a PenB that is more robust than that present in susceptible isolates, as well as other resistance factors. Curiously and diagnostic for the two complexes, both Bpc and Bcc bacteria contain distinct annotated PenA class A β-lactamases. However, the protein from Bcc bacteria is missing its essential active-site serine and, therefore, is not a β-lactamase. Regulated expression of a transcriptional penB′-lacZ (β-galactosidase) fusion in the B. pseudomallei surrogate B. thailandensis confirms that although Bpc bacteria lack an inducible β-lactamase, they contain the components required for responding to aberrant peptidoglycan synthesis resulting from β-lactam challenge. Understanding the diversity of antimicrobial resistance in Burkholderia species is informative about how the challenges arising from potential resistance transfer between them can be met. IMPORTANCE Burkholderia pseudomallei causes melioidosis, a tropical disease that is highly fatal if not properly treated. Our data show that, in contrast to B. pseudomallei, B. ubonensis β-lactam resistance is fundamentally different because intrinsic resistance is mediated by an inducible class A β-lactamase. This includes resistance to carbapenems. Our work demonstrates that studies with near-neighbor species are informative about the diversity of antimicrobial resistance in Burkholderia and can also provide clues about the potential of resistance transfer between bacteria inhabiting the same environment. Knowledge about potential adverse challenges resulting from the horizontal transfer of resistance genes between members of the two complexes enables the design of effective countermeasures.